ANALISIS PENGARUH UTANG DOMESTIK DAN UTANG LUAR NEGERI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA PADA TAHUN 2014 - 2023 - Pratomo, Athar Gherin; Fadjar, Nurman Setiawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
During the period of 2014-2023, Indonesia government set a target for average economic growth of 5.2% for 2014-2020 and 6% for 2020-2025. In order to achieve that, the fiscal policy adopted by the government is by utilizing debt. Based on Keynesian view, the government can incur debt to finance government budget deficits and stimulate economic growth. This research employs the ordinary least squares (OLS) method because it seeks to analyze the relationship between the variables of quarterly increase of GDP, quarterly increase of domestic debt growth, and quarterly foreign debt. Based on the estimation results of the model conducted in the research, the result show that the variables of quarterly domestic debt growth and quarterly foreign debt growth can only explain a 14.49% increase in quarterly GDP value. Simultaneously, domestic debt and foreign debt do not affect economic growth. Partially, an increase per quarter in domestic debt has a significant negative effect on the increase in quarterly GDP value, while an increase per quarter in foreign debt has a positive but not significant effect on the increase of quarterly GDP value.